Real‐World Use of Prophylactic Antibiotics in Insertable Cardiac Monitor Procedures. Issue 8 (7th June 2016) - BEINART, SEAN C.; NATALE, ANDREA; VERMA, ATUL; AMIN, ALPESH; KASNER, SCOTT; DIENER, HANS‐CHRISTOPH; POULIOT, ERIKA; FRANCO, NORELI; MITTAL, SUNEET
Abstract : Background: The use of prophylactic antibiotics during insertable cardiac monitor (ICM) procedures is a carryover of the common practice used with therapeutic cardiac implantable electronic devices. We sought to characterize the current practice of ICM insertion procedures to evaluate the influence of prophylactic antibiotic administration on the occurrence of infections. Methods: We characterized insertion procedures and procedure‐related infections from an ongoing multicenter registry (Reveal LINQ TM Registry). In order to accurately capture infections, only patients enrolled before or the day of insertion who also had a record of whether or not preoperative antibiotics were used were included in this analysis. Infections were defined based on the physician's assessment and reported upon occurrence. Patients were categorized into two analysis cohorts based on prophylactic antibiotic use. Results: We analyzed 375 patients from 14 U.S. centers (age 63.1 ± 15.6 years; male 54.1%). Approximately two‐thirds of patients (66.4%) did not receive any preprocedural antibiotics. The overall infection rate was 1.1% (0.3–2.7% confidence interval [CI]) and corresponded to four events. In the group that did not receive preprocedural antibiotics, there were two minor infections (0.8%, [0.1–2.9% CI]), whereas in the group receiving preprocedural antibiotics a serious and a minor infection occurred (1.6%, [0.2–5.6% CI]); this serious infection resulted in an explant. Conclusions: Current real‐world practice shows that ICM insertions are increasingly performed without the use of prophylactic antibiotics, which is associated with a very low infection rate.